ANALYSIS OF THE EFFECT OF EMPLOYEE PERFORMANCE, TURN OVER INTENTION ON ORGANIZATIONAL COMMITMENT DURING THE COVID-19 PANDEMIC - Asri, Cahya Purnama (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study examines the Analysis of the Effect of Employee Performance, Turnover Intention on Organizational Commitment During the Covid-19 Pandemic. This research was conducted on companies in Yogyakarta, the sample used in this study was 60, and the analytical tool used was using SPSS 22 software as the tool. Is there a positive influence between employee performance on organizational commitment, is there a positive influence on turn over intention on organizational commitment, is there a positive influence on employee performance on organizational commitment through turnover intention as a mediator, in companies in Yogyakarta